STUDENTS’ PERCEPTIONS IN WILLINGNESS TO COMMUNICATE IN EFL CLASSROOM - Andayani, Widya; Perangin-angin, Alemina Br.; Nasution, Rafika Dewi; Debora, Marisi; Hartati, Rita (Annual International Conferences on Language, Literature, and Media, 2022)
This article explores learners' perceptions of their speaking ability, contributions to oral class activities in the EFL classroom, and attitudes toward these activities, as well as how these perceptions and attitudes influenced learners' readiness to communicate in the L2. The study used a variety of data collection instruments, but the online interview was the primary source of data. This study included twenty students from the English department (L2). During the online interview, students were asked to reflect on their opinions of problems encountered when studying and speaking in an EFL classroom. It was discovered that lack of vocabulary (35%) fluency (25%), anxiety (15%), grammar (10%), pronunciation (10%), and use of English with peers (5%) are the elements that make pupils feel uneasy when speaking in English. The findings of this study show that students' perceptions of the speaking activities and of themselves as learners in the foreign language classroom influenced their readiness to communicate in a variety of ways. In general, as learners' self-esteem grew, so did their readiness to use the L2 in class